INTERGEO 2015 l'evoluzione/rivoluzione del settore geospaziale - Bernardini, Fulvio (GEOmedia, 2015)
Intergeo proves once again to be the most important globally event of the geospatial industry. 2015 edition has been held in Stuttgart from the 15th to the 17th of september 2015. With more than 16.000 attendees and 545 exhibitors Intergeo's edition will be remembered for the introduction of the concept of Geospatial 4.0.